A polyacrylonitrile copolymer-silica template for three-dimensional hierarchical porous carbon as a Pt catalyst support for the oxygen reduction reaction. Issue 30 (19th July 2017) - Liu, Minmin; Li, Jian; Cai, Chao; Zhou, Ziwei; Ling, Yun; Liu, Rui
Abstract : Herein, we report a novel route to construct a hierarchical three-dimensional porous carbon (3DC) through a copolymer-silica assembly. Abstract : Herein, we report a novel route to construct a hierarchical three-dimensional porous carbon (3DC) through a copolymer-silica assembly. In the synthesis, silica acts as a hard template and leads to the formation of an interconnected 3D macropore, whereas styrene- co -acrylonitrile polymer has been used as both a carbon source and a soft template for micro- and meso-pores. The obtained 3DC materials possess a large surface area (∼550.5 m 2 g −1 ), which facilitates high dispersion of Pt nanoparticles on the carbon support. The 3DC-supported Pt electrocatalyst shows excellent performance in the oxygen reduction reaction (ORR). The easy processing ability along with the characteristics of hierarchical porosity offers a new strategy for the preparation of carbon nanomaterials for energy application.